The Impact of Financial Literacy Dimensions on Youths’ Financial Well-Being - Susanto, Alicia Caitlyn (Industrija, 2025)
The purpose of the research is to assess how financial literacy affects young people’s well-being in accordance with the Theory of Planned Behavior (TPB). This research was designed to investigate how the theory’s conception functions in the context of Indonesian youths, based on the theory’s conceptual framework. The statistical analysis was performed on the sample of 150 respondents. To investigate this research idea, Partial Least Squares – Structural Equation Modeling (PLS-SEM) was selected. Financial well-being is positively impacted by one’s financial attitude. Financial well-being is also influenced by financial behavior. However, financial knowledge has no impact on financial well-being. The research’s findings contribute to the literature by adding another empirical confirmation from Indonesian youths’ viewpoint. It offers useful information and provides youths with financial literacy skills. This research also contributes to the advancement of knowledge in relation to the financial literacy in youths. It could help governments to make decisions on youth financial well-being. Moreover, it highlights the direction which a government or policymaker can take to pursue youth financial literacy and its well-being.